Pengaruh Profitabilitas, Likuiditas, Struktur Modal dan Tata Kelola Perusahaan Terhadap Nilai Perusahaan Pada Sektor Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Annisa Dwi Putri Annisa; Nora Susanti; Yesmira Syamra (Jurnal Ecogen, 2025)
The objective of this project is to promote collective health through occupational therapy, focusing on mechanics, operators, and supervisors. This initiative aims to enhance the technical skills of personnel and increase the value of infrastructure companies listed on the Indonesia Stock Exchange from 2019 to 2023. The research is quantitative, with the population consisting of all infrastructure sector companies listed on the Indonesia Stock Exchange, totaling 70 companies. Purposive sampling was used for data collection. The findings reveal: (1) Profitability does not significantly influence company value. (2) Liquidity also does not significantly affect company value. (3) Capital structure has a significant impact on company value. (4) Corporate governance does not significantly influence company value. (5) Collectively, profitability, liquidity, capital structure, and corporate governance significantly affect company value in infrastructure sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. The F-test results indicate that these variables have an Fstatistic values of 3.02234 and a probability value of 0.019597, which is less than 0.05.